ANALISIS PENGARUH TERJADINYA AUDIT DELAY PADA PERUSAHAAN SARANA DAN PRASARANA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - CHANIA AULIA; Erma Setiawati (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Abstract In Indonesia, the capital market has experienced a significant increase, marked by the issuance of shares to the general public by companies going public. Increased development has an impact on increasing demand for financial statement audits. The aim of this study is to analyze the effect of company size, profitability, solvency, audit committee, and earnings per share on audit delay. Case studies of facility and infrastructure companies listed on the Indonesia Stock Exchange in 2019 - 2021. The sample used in this research is infrastructure companies and infrastructure in the Property, Real Estate, and Building Construction, Building Infrastructure, Utilities dan Transportation sub-sectors on the Indonesia Stock Exchange (IDX) for the period 2019 - 2021. Simultaneous test results show that Company Size, Profitability, Solvency, Audit Committee, and Earning Per Share have a significant effect on Audit Delay in Facilities and Infrastructure Companies Listed on the Indonesia Stock Exchange in 2019 - 2021. Partially shows that Solvency has a significant negative effect on Audit Delay in Facilities and Infrastructure Companies Listed on the Indonesia Stock Exchange in 2019 - 2021. The Audit Committee has a positive effect Significant Against Delay Audit Facilities and Infrastructure Companies Listed on the Indonesia Stock Exchange in 2019 -2021. Company Size, Profitability, and Earning Per Share have no significant effect on Audit Delay in Facilities and Infrastructure Companies Listed on the Indonesia Stock Exchange in 2019 - 2021.